Exploration on Cultivating Students’ Innovative Ability in Flash Animation Teaching - Gao, Yongli (Journal of Theory and Practice of Contemporary Education, 2024)
ting students' innovative ability, and how to inspire students, carry out bold creativity, and finally complete a specific project. This paper proposes to create an innovative environment, reform teaching methods, establish a flexible assessment mechanism, and carry out appropriate competition activities to comprehensively improve students' independent innovation ability.